Puzzle of India's governance - Mitra, Subrata K. (London, 2006)
The book brings together material that I have collected over the past ten years. During these years, I have taught, supervised, changed jobs and countries, and worked on other writing projects (Legitimacy and Conflict in South Asia, 1997, and Culture and Rationality and Democracy and Social Change, both published in 1999).
Keywords: Governance